The moderating role of perseverance and determination in action in the context of self-efficacy and life satisfaction of sportspeople with mobility impairment - Natalia SEGIET; Krzysztof GERC (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: The article assumes the biopsychosocial model of disability and refers, inter alia, to the assumptions of the concept of empowerment, which recognizes the fact that practicing sports by people with disabilities creates favorable conditions for strengthening resources and developing skills. An attempt was made to develop a model that verifies the moderating importance of mental resilience in the aspect of experiencing a sense of effectiveness and life satisfaction in sportspeople with mobility impairment. Material and method: The research conducted in an encrypted online manner involved 58 people (31 able-bodied sportspeople and 27 sportspeople with physical disabilities). The following tools were used in this study: the Satisfaction with Life Scale (SWLS), the General Self-Efficacy Scale (GSES), the Positivity Scale (P Scale), the Resilience Scale (RS 25) and a demographic questionnaire. The conducted exploratory analyses which ultimately constitute the basis of the mathematically verified model of interactions between the variables identified in the study, as proposed in the article, showed a statistically significant influence of the RS 25 subscale Perseverance and determination in action as a moderator, both in relation to variables, physical disability and life satisfaction, as well as relationships between the variables of motor impairment and self-efficacy. Results: Having taken into consideration group abundance, strength of the effect and statistical significance, it is possible to make attempts to generalize findings of this study into the general population of athletes. Modelling based on subscales turned out to be the most adequate one, as it allowed discovering more in-depth relations between variables. Conclusions: Statistical analysis confirmed the assumed lack of differences between athletes with and without disabilities regarding the life satisfaction variable. It did not confirm that athletes with disabilities had higher scores in the self-efficacy variable (in GSES questionnaire) than regular athletes. It is important to note that physical disability or lack of it moderated by perseverance and determination influences both life satisfaction and self-efficacy in a statistically significant way. Based on conducted statistical analysis, in relations to the initially presented model, the mathematically revised model of confirmed interactions and relations between variables was proposed.